The reliability and quality of YouTube videos as a source of breath holding spell - Mehmet Semih Demirtas; Nurettin Alici (BMC, 2024)
Abstract Background Breath holding spells (BHS) are an important non-epileptic condition that is common in childhood and causes concern to families. YouTube is a powerful social media tool for accessing diseases and information such as BHS in child health. The aim of the study was to measure of the quality and reliability levels of the videos published in English on BHS uploaded on YouTube. Methods The key words "infant", "cry", "breath holding spells", holding spells" and "breath spells" were searched on the YouTube on November 14, 2022, in this study. Along with the general features of the videos, their quality and reliability were evaluated according to the global quality score (GQS), mDISCERN score. Results Fifty-five videos were evaluated. The mDISCERN and GQS scores of the videos in the useful group were higher than those in the misleading group (p < 0.001, p < 0.001). In the useful group, 87.5% of academic institutions and 93.3% of medical doctors (MDs) uploaded high-score GQS videos, while this rate was 16.7% in independent users (p = 0.005). The positive correlation was found between mDISCERN and GQS scores (p < 0.001). Conclusion The majority of YouTube videos on BHS contained useful information with sufficient quality. Professional associations such as universities and academic institutes need to produce better quality videos to provide families/users with more accurate and up-to-date information about BHS. We emphasize that YouTube should analyse videos published in the field of health, especially in the field of pediatrics, such as BHS, with committees consisting of expert health professionals, and publish them after evaluation. YouTube should consider collaborating with professional pediatrics health organizations such as American Academy of Pediatrics (AAP), academic institutes and universities in the field of BHS to produce high-quality videos.